If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sec * x + -1secx + -2 = 0 Multiply ces * x cesx + -1secx + -2 = 0 Reorder the terms: -2 + cesx + -1cesx = 0 Combine like terms: cesx + -1cesx = 0 -2 + 0 = 0 -2 = 0 Solving -2 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2(2y+1)=(5y-2) | | 5x+9+4x=9+8+(-7) | | log(9x^3)=2 | | 7a^2-5a-5=-5 | | X^2-25=10 | | 2(25-5)=2(26+5) | | 5x+9+4x=9+8 | | 21/3×5-11 | | 2/7=x/7 | | (X^-3y^3)^-4/(y^3x^-5)^-5 | | 8x^(13/3)-24=0 | | 2*cosx=2*cos*2x | | 12z-4x=-7 | | 10h-10=10-10h | | x^9/2 | | 38x+66=180 | | 3x-(5x)= | | 2n-4=5n+5 | | 80x^2-720=0 | | 8=3x+bx | | 12z+4x=-7 | | 27q-9=180 | | 112x^2-56x=0 | | 2y-7=5-y | | x+.7y=238 | | z=2+3i | | 6n+3+15n+48+3n+10= | | 16r^2-121=0 | | 2/7x7/1 | | 4=(1/4)ax | | 9v-2+2(2v+9)=-2(v+1) | | 12=2x^2-x |